Peran Wanita Tani Pembuat Atap Rumbia dalam Meningkatkan Pendapatan Keluarga dalam Perspektif Ekonomi Islam (Studi Kasus di Kabupaten Konawe) - Beti Mulu; Leni Saleh (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
This study aimaed ti analyze : (1) how much revenue the thatched roof maker of womenfarmers in increasing family incomes in Konawe, (2) how the role of women farmers in thethatched roof maker Konawe in the perspective of the Islam ekonomiy. Data collectiontechniques uses two ways : primary data through direct interviews using a questionnaire toa sample of respondents and secondary data obtained from recompilation literature andbibliography. Data collected were processed using descriptive statistical analysis and toanalyze how much the revenue from the women farmers in district Konawe use quantitativemethods of analysis.This study concluded that the results of the analysis showed revenue earned income ofwomen farmers maker thatched roof in Konawe already quite optimal amountingRp.23.248.175 or an average of Rp.1.010.790 one person women farmers in an effort to makethe thatched roof in a month the manufacturing process. The work done by women farmersmaker thatched roofs in increasing family income is a good business and in line withIslamic law becouse it is done with effort and good intentions, which is to help boost theeconomiy of the family income, while permission form her husband. So it does not conflictwith principles of Islamic economics, in fact, Islam forbids the muslims to stand by or asksas beggars, the homeless and other people while still being able to strive.